2010
DOI: 10.1152/japplphysiol.91429.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric hyperoxia and normobaric reoxygenation increase excitability and activate oxygen-induced potentiation in CA1 hippocampal neurons

Abstract: Breathing hyperbaric oxygen (HBO) is common practice in hyperbaric and diving medicine. The benefits of breathing HBO, however, are limited by the risk of central nervous system O2 toxicity, which presents as seizures. We tested the hypothesis that excitability increases in CA1 neurons of the rat hippocampal slice (400 microm) over a continuum of hyperoxia that spans normobaric and hyperbaric pressures. Amplitude changes of the orthodromic population spike were used to assess neuronal O2 sensitivity before, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 82 publications
9
56
0
Order By: Relevance
“…In slices of mature animals, it has been shown that the efficacy of synaptic functioning (Garcia III et al, 2010) and network activity (Hajos et al, 2009) correlates strongly with the level of tissue oxygenation. Whether synaptic function in the neonatal network depends significantly on oxidative metabolism or whether its energy needs can be covered by glycolysis alone is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…In slices of mature animals, it has been shown that the efficacy of synaptic functioning (Garcia III et al, 2010) and network activity (Hajos et al, 2009) correlates strongly with the level of tissue oxygenation. Whether synaptic function in the neonatal network depends significantly on oxidative metabolism or whether its energy needs can be covered by glycolysis alone is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Neural tissue O 2 -depth profiles have been previously reported in vivo (for summary see Garcia 3rd et al 2010), in situ in the working heart-brain stem preparation (Wilson et al 2001), as well as in vitro in both isolated brain stem-spinal cord preparations (Brockhaus et al 1993;Okada et al 1993) and brain slices (Bingmann and Kolde 1982;Garcia 3rd et al 2010;Mulkey et al 2001). Several factors influence the degree of in vitro tissue oxygenation within a brain slice.…”
Section: In Vitro Tissue Oxygenationmentioning
confidence: 97%
“…Although only a handful of brain slice studies have shown that neuronal activity is affected throughout a broad range of O 2 tensions outside of hypoxia (0% O 2 ) and the conventional control condition (95% O 2 ), these studies have shown that graded changes in O 2 , and not only hypoxia, can influence biochemical activity (D'Agostino 2007;Fowler 1993) and excitability of neurons within local networks (Fowler 1993;Garcia 3rd et al 2010;Hoffmann et al 2006;Mulkey et al 2001). Similarly, in invertebrate systems, small changes in oxygenation also have been shown to influence network activity (Clemens et al 2001).…”
Section: In Vitro Tissue Oxygenationmentioning
confidence: 99%
“…By contrast, it was shown that hyperoxia leads to the activation of population spikes and synchronous interictal discharges in CA1 hippocampal region [18]. Oxygen-induced plasticity may play a substantial role in the pathogenesis of CNS.…”
Section: Discussionmentioning
confidence: 96%